Inline Waveguide Sharp-Rejection Bandpass Filters With Transmission Zeros Using Resonant Coupling Slots - Lubina Iram; Muhammad Yameen Sandhu; Adam Lamecki; Roberto Gomez-Garcia; Michal Mrozowski (IEEE Access)
This work presents a design methodology for synthesizing a category of compact inline sharp-rejection waveguide cavity bandpass filters based on novel frequency-variant coupling (FVC) structures. These FVCs consist of a rectangular slot placed in the top broadwall of the WR-90 rectangular waveguide and loaded with an additional top cavity above the slot coupled through the slot. Both the slot and the top cavity resonate in the vicinity of the filter passband and can produce TZs at their resonance frequencies. The top cavity could be arranged either symmetrically or asymmetrically along the reference plane to excite or suppress the cavity $TE_{101}$ mode, respectively. A double-zero-single-pole (DZSP) response can be achieved by either placing two cavity-loaded slots on opposite broadwalls of the main waveguide or by asymmetrically placing a single cavity-loaded slot on one broadwall. The asymmetry perturbs the field-pattern distributions of the $TE_{100}$ slot and $TE_{101}$ cavity modes with regard to the symmetrical case so as to convert them into hybrid slot-and-cavity modes—referred to as S&CM 1 and S&CM 2. This approach excites both S&CM resonances to obtain the DZSP filtering transfer function with size-compactness advantage. Two fifth-order inline waveguide bandpass filter prototypes are designed at the electromagnetic (EM) simulation level based on DZSP-slot-mode (DZSP-SM) and DZSP-slot-and-cavity-mode (DZSP-S&CM) FVCs, respectively. A proof-of-concept prototype of fifth-order sharp-rejection waveguide bandpass filter using a DZSP-S&CM FVC, which is centered at 10 GHz and exhibits a pair of close-to-passband TZs, is manufactured and characterized. The measured results are in good agreement with the EM-simulated results, thus fairly verifying the viability of the devised filter design concept.